Proposed an upgrading work of 1926 Heritage Hotel for Anggerik Lodging Sdn Bhd at 227 Jalan Burma, 10050 Georgetown, Ipoh. / Siti Nor Farazziani Che Ahmad - Che Ahmad, Siti Nor Farazziani (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose upgrading work of 1926 Heritage Hotel for Anggerik Lodging Sdn Bhd at 227 Jalan Burma, 10050 Georgetown, Penang. This upgrading work of 1926 Heritage Hotel is to attract customers to come to this hotel. The target markets for the user of this hotel are among the local and foreigners. Because of the customers that come to stay in the hotel are from different place, amount and status,the variety of services will help them to choose for their comfort. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the customers to stay in the 1926 Heritage Hotel. Connected to that, the chosen design style for 1926 Heritage Hotel based on 1926 era at Penang. Specific image for this hotel will able attract people to come agagin and again to this hotel. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers, types of services offered, rate for every type of rooms, operation time and informations about other hotel that use the gives same services as 1926 Heritage Hotel. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.